South Korea: Successful large-scale international borrower - Klaus Fertig (Intereconomics, 1983)
At the end of 1982 South Korea had foreign debts of US 38 billion, the third highest total for a developing country after those of Mexico and Brazil. In contrast to these countries, however, South Korea has avoided debt crises so far. In view of the 20 or more rescheduling operations carried out in 1982, the country is at present a model for a successful programme of borrowing. The development of this Far Eastern country therefore deserves closer examination.
Keywords: 330; Indebtedness